Biofortified rice program of the Alliance Bioversity and CIAT: Progress and perspectives - Sandoval, Leydi; Bartholomé, Jerome; Borrero, Jaime; Grenier, Cecile (2024)
The growing global demand for rice drives the search for new materials with high yields, resistance to pests and diseases, grain quality, and high nutritional content. For over 20 years, the biofortified rice program of CIAT and later the Alliance has contributed to global food security by developing lines with greater nutritional value and high agronomic quality standards.The objective of this work is to describe the program, its evolution, and its achievements. Over time, the program has identified and distributed high-potential lines to various partners. Additionally, it has incorporated breeding strategies aimed at increasing the genetic gain of zinc content by at least 1.86% per year.The program's first phase began with the Agrosalud project in 2005, which sought to increase iron and zinc content in polished rice grains. Since then, nutritional quality has been included as a selection criterion, and evaluation protocols have been established. Subsequently, around 2013, another phase started, during which the zinc content of over 2,000 accessions from the germplasm bank was analyzed. Once the best genotypes were identified, advanced biofortified lines were developed through crossings and selection schemes, which were evaluated in multi-environment trials.Thanks to the collaboration of entities such as CIRAD, HarvestPlus, and INIAS from different countries, four varieties have been released in Latin America. This joint effort has even crossed borders, enabling the release of a high-zinc variety in Mali, Africa. Currently, the program continues to advance in diversification and genetic gain through breeding processes and tools, such as the use of molecular markers, DNA sequencing, and genome editing. These efforts not only aim to develop new lines but also to encourage partner participation in improving the program.